2021
DOI: 10.1021/acs.orglett.1c00631
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Hydroacyloxylation/Ring-Opening Reaction of Ynamides, Acids, and Aziridines

Abstract: A highly enantioselective three-component reaction of ynamides with carboxylic acids and 2,2′-diester aziridines has been realized by using a chiral N,N′-dioxide/Ho­(OTf)3 complex as a Lewis acid catalyst. The process includes the formation of an α-acyloxyenamide intermediate through the addition of carboxylic acids to ynamides and the following enantioselective nucleophilic addition to in-situ-generated azomethine ylides induced by the chiral catalyst. A range of amino acyloxyenamides are delivered in moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Control experiments demonstrated that the use of Mn­(OAc) 3 and, in addition, a degassed solvent was mandatory for the reaction to proceed. The use of 2.2 equiv of Mn­(III) in acetic acid at 40 °C led after 24 h to a mixture of furan 3aa and enamide 4a , resulting from the addition of acetic acid to ynamide, in a 1:1 ratio determined from the 1 H NMR spectrum of the crude reaction mixture (entry 1). Moving from acetic acid to dichloromethane (CH 2 Cl 2 ) aprotic medium prevented the formation of 4a , but a significant amount of ynamide 1a was recovered even after reaction for 48 h (entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…Control experiments demonstrated that the use of Mn­(OAc) 3 and, in addition, a degassed solvent was mandatory for the reaction to proceed. The use of 2.2 equiv of Mn­(III) in acetic acid at 40 °C led after 24 h to a mixture of furan 3aa and enamide 4a , resulting from the addition of acetic acid to ynamide, in a 1:1 ratio determined from the 1 H NMR spectrum of the crude reaction mixture (entry 1). Moving from acetic acid to dichloromethane (CH 2 Cl 2 ) aprotic medium prevented the formation of 4a , but a significant amount of ynamide 1a was recovered even after reaction for 48 h (entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…Li and coworkers, 8 which combine aldehyde/ketone, terminal alkyne and amine into propargylamine in a one-pot transition metal-catalysed coupling (Scheme 1, top). 9,10 Replacing the alkyne component by a terminal ynamide 11,12 could lead to a one-pot synthesis of γ-amino-ynamides (Scheme 1, bottom). This approach was driven by the following reasoning: (i) despite its interest, 13 accesses to the latter scaffold are so far limited and based on multi-step sequences, 14 a simpler way would thus be beneficial and probably open up new perspectives; (ii) since ynamides are more nucleophilic than alkynes (see N parameters), 15,16 they should be more reactive in A 3 /KA 2 -type reactions; (iii) although green by essence (see above), 8 A 3 /KA 2 reactions could be made greener by avoiding solvent and/or by using recyclable catalyst.…”
Section: Introductionmentioning
confidence: 99%